The dutch national clinical audit for lung cancer: A tool to improve clinical practice? An analysis of unforeseen ipsilateral mediastinal lymph node involvement in the Dutch Lung Surgery Audit (DLSA). Issue 6 (June 2018) - Heineman, David Jonathan; Beck, Naomi; Wouters, Michael Wilhelmus; van Brakel, Thomas Jan; Daniels, Johannes Marlene; Schreurs, Wilhelmina Hendrika; Dickhoff, Chris
Abstract: Objective: Optimal treatment selection for patients with non-small cell lung cancer (NSCLC) depends on the clinical stage of the disease. Particularly patients with mediastinal lymph node involvement (stage IIIA-N2) should be identified since they generally do not benefit from upfront surgery. Although the standardized preoperative use of PET-CT, EUS/EBUS and/or mediastinoscopy identifies most patients with mediastinal lymph node metastasis, a proportion of these patients is only diagnosed after surgery. The objective of this study was to identify all patients with unforeseen N2 disease after surgical resection for NSCLC in a large nationwide database and to evaluate the preoperative clinical staging process. Methods: Data was derived from the Dutch Lung Surgery Audit. Patients with pathological stage IIIA NSCLC after an anatomical resection between 2013 and 2015 were evaluated. Clinical and pathological TNM-stage were compared and an analysis was performed on the diagnostic work-up of patients with unforeseen N2 disease. Results: From 3585 patients undergoing surgery for NSCLC between 2013 and 2015, a total of 527 patients with pathological stage IIIA NSCLC were included. Of all 527 patients, 254 patients were upstaged from a clinical N0 (n = 186) or N1 (n = 68) disease to a pathological N2 disease (7.1% unforeseen N2). In these 254 patients, 18 endoscopic ultrasounds, 62 endobronchial ultrasounds and 67 mediastinoscopies were performed preoperatively. Conclusions: In real world clinical practice in The Netherlands, the percentage of unforeseen N2 disease in patients undergoing surgery for NSCLC is seven percent. To further reduce this percentage, optimization of the standardized preoperative workup is necessary.